Reconstruction of Back Defect from Giant Congenital Melanocytic Nevus Using Dermal Substitute Matrix - Kareem W. Makkawi, MD; Paul T. Beaineh, MD; Saif E. Emsieh, MD; Edwin E. Chrabieh, BS; Amir E. Ibrahim, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Giant congenital melanocytic nevi are large pigmented premalignant lesions present at birth that have an associated risk of malignant transformation. Full-thickness excision of these lesions would be required to eliminate this risk. However, giant nevi can leave behind large defects that can be challenging to reconstruct. We present the case of a pediatric patient with a lesion occupying the entirety of the back, or around 18% total body surface area, and in whom Integra and meshed skin grafts were successfully used. This represents the largest defect size in the literature resulting from a giant nevus that has been treated by this method. Full take of the skin grafts was observed 26 days from the excision of the lesion with satisfactory functional outcomes.